2020
DOI: 10.3390/ani10081435
|View full text |Cite
|
Sign up to set email alerts
|

Changing Human Behavior to Improve Animal Welfare: A Longitudinal Investigation of Training Laboratory Animal Personnel about Heterospecific Play or “Rat Tickling”

Abstract: Despite evidence for rat tickling’s animal welfare benefits, the technique is rarely implemented in part because of a lack of training. This study’s purpose was to determine the efficacy of online-only or online + hands-on training programs on key outcomes for rat tickling in comparison to a waitlist control condition. After completing a baseline survey, laboratory animal personnel currently working with rats in the United States were semi-randomized to receive online-only training (n = 30), online + hands-on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Accordingly, goats trained by this group achieved the target behaviour more closely. This is in agreement with LaFollette et al ( 2020 ) who evaluated different educational programmes to implement rat tickling in an animal facility as refinement technique. Their study showed that participants with hands-on training education learned more effectively than participants trained purely online.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, goats trained by this group achieved the target behaviour more closely. This is in agreement with LaFollette et al ( 2020 ) who evaluated different educational programmes to implement rat tickling in an animal facility as refinement technique. Their study showed that participants with hands-on training education learned more effectively than participants trained purely online.…”
Section: Discussionsupporting
confidence: 92%
“…Challenges to implementation itself include scientific barriers, such as the limitations of a given method; legal barriers, such as the "gold standard" of animal use in regulatory testing; economic barriers, such as the financial costs and time resources for implementing new approaches; cultural and institutional obstacles, such as difficulties establishing evaluation criteria for academic success that reward 3Rs implementation; and difficulties changing the established mindset. Ongoing efforts to address these issues [e.g., (61)(62)(63)(64)] are being made, but the examples are still rare. There are also barriers at the individual and laboratory level, where animal research is sometimes still seen as the nimbus of "serious research. "…”
Section: Complexities Of Implementation: Overcoming Barriersmentioning
confidence: 99%
“…Additionally, personnel were mentioned as the single most important factor that enabled widespread adoption of refined handling. Therefore, both this survey and prior research [ 23 ] further indicates the importance of convincing people and providing training to increase refinement implementation.…”
Section: Discussionmentioning
confidence: 76%
“…A commonly stated barrier to refined handling was the perception that it would take more time to handle mice. A time barrier has been identified in several prior studies of refined rodent handling [ 19 , 20 , 23 , 30 ]. This perception may be due to time required to learn a new technique and early research requiring 30 s plus habituation time for refined methods [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation